2018
DOI: 10.17015/ejbe.2018.021.07
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Intellectual Capital on Financial Performance and Market Value: Evidence from Turkey

Abstract: In this study we aim to examine the effects of intellectual capital and its components on companies' market value and financial performance in Turkey. The financial and market data of production companies listed in Borsa Istanbul 100 index (BIST-100) for the periods 2011 through 2014 are used as dataset. We selected three different measures for financial performance; ROA, ROE and Net Profit Margin, and one measure for market value; Market to Book Ratio. As independent variables, we firstly took Modified Value … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
12
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 19 publications
6
12
1
Order By: Relevance
“…Overall models are significance, nevertheless, its ability to explain the overall variability in the M/B ratio is low; about 5.64%, and EPS 39.13%. Previous studies also found insignificant between M/B and HCE and SCE (Yilmaz & Acar, 2018). The findings contradict previous studies, (Smriti & Das, 2017;Ghosh & Maji, 2015; indicate a positive relationship between HCE and M/B ratio.…”
Section: Resultscontrasting
confidence: 71%
“…Overall models are significance, nevertheless, its ability to explain the overall variability in the M/B ratio is low; about 5.64%, and EPS 39.13%. Previous studies also found insignificant between M/B and HCE and SCE (Yilmaz & Acar, 2018). The findings contradict previous studies, (Smriti & Das, 2017;Ghosh & Maji, 2015; indicate a positive relationship between HCE and M/B ratio.…”
Section: Resultscontrasting
confidence: 71%
“…Based on regression analysis, the results in Model 1 indicate that VAIC TM has a positive effect on firm performance indicator (M/B), thereby supporting H1. When RCE is entered into the model 3, the results reveal that RCE also have a positive impact on M/B, which supports previous studies (Ulum et al, 2014(Ulum et al, , 2017Yilmaz & Acar, 2018)which is between -21.41 until 5.20. Based on M-VAIC scores, performance of IC is classified into four, namely Top Performers, Good Performers, Performers Common, and Bad Performers.…”
Section: Discussionsupporting
confidence: 86%
“…Hence, multicollinearity appears not to be a serious concern in this study. The results of correlation analysis are consistent with the results in Dženopoljac et al (2016); Dzenopoljac et al(2017); Ozkan et al (2017); Yilmaz & Acar (2018) and Zulkifli et al (2017), but differ from Smriti & Das (2017).…”
Section: Correlation Analysissupporting
confidence: 84%
See 1 more Smart Citation
“…Chen, Cheng, and Hwang (2005), Nazari and Herremans (2007) and Tan, Plowman, and Hancock (2007) have emphasised that IC measures are still in an exploratory stage and a coherent measuring technique for IC has not been formulated yet. However, the Value Added Intellectual Coefficient (VAIC) method has gained recognition as the most efficient (Chan, 2009), and widely adopted (Zhicheng et al, 2016;Yilmaz & Acar, 2018) measure amongst an array of measures (see Table 1) available to value IC.…”
Section: Introductionmentioning
confidence: 99%